Bone Marrow Metastasis- Morphology, Molecular features and Diagnosis: A Study from a regional cancer Centre in India - Rajakumar, Namrata. N. (Tropical Journal of Pathology and Microbiology, 2024)
Objective: bone marrow biopsies are frequently done for histologically documented malignancies for staging also in suspected malignancies Bone marrow involvement by solid tumor implicates advanced disease and bad prognosis..It is important to rule out bone marrow involvement before planning for any definitive ,curative treatment hence diligent and exhaustive search for metastatic cells in Bonemarrow which aids in accurate staging treatment and prognosis was done. Materials and Methods: This was a retrospective observational study of bone marrow involvement by , solid tumors and their hematological manifestation Results: Evaluation of Bone marrow evaluation during past 7 years , in solid malignancies,revealed Out of 772, 342 were pediatric cases and 430 were adult cases. Bone marrow was involved in 82 patients, In adults, bone marrow involvement was diagnosed in 40 cases. Neuroblastoma was the most common malignancy, which involved the bone marrow in pediatric cases..In adults common was neuroendocrine carcinoma metastasis to bone marrow followed by carcinoma breast in women and carcinoma prostate in men. Conclusion: A diligent and exhaustive search for metastatic cells in Bonemarrow helps in accurate staging treatment and prognosis ,morphological examination is still the gold standard for suspected marrow involvement ,Use of immunohistochemistry markers on bone marrow biopsies results in higher detection rate,also aids in picking very few neoplastic cells ,thereby helps in detecting early metastasis. Immunohistochemistry may be useful in recognizing some tumors in marrow and confirmation of primary tumor origin..